Pengaruh Risiko Kredit Dan Kecukupan Modal Terhadap Likuiditas Suatu Perusahaan (Studi Kasus Di Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia) - Adinda Siti Salsya Az-zahra; Acep Suherman; Tina Kartini (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
The Covid 19 pandemic has increased pressure on four sectors in Indonesia, including the financial sector such as Banking. The financial sector, especially the banking industry, has the responsibility to collect and redistribute these funds to the public. During the pandemic, banks had an impact on financial performance, especially non-performing loans and liquidity due to hampered credit disbursement. In order to increase economic growth again after the pandemic, it is important for banks to increase the amount of credit available. Of course, at this stage of recovery, banks also try to provide financial performance reports as best as possible by paying attention to the risks that may arise, sufficient capital to help the company's operations and manage its liquidity. This is because sufficient capital can help cover the risks that arise and allow banks to distribute more credit without hindering liquidity. Companies can look for credit risk values using NPL ratios, capital adequacy with CAR ratios, and liquidity using LDR ratios. NPLs can show a ratio indicator for companies to evaluate the potential for credit risk. In addition, the CAR ratio shows whether the bank has sufficient capital to meet its operational needs as well as bear the risk. Meanwhile, the LDR ratio is to maintain whether the company's liquidity level is still at the limit or safe area.